2007
DOI: 10.1111/j.1744-6570.2007.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

In Support of Personality Assessment in Organizational Settings

Abstract: Personality constructs have been demonstrated to be useful for explaining and predicting attitudes, behaviors, performance, and outcomes in organizational settings. Many professionally developed measures of personality constructs display useful levels of criterion‐related validity for job performance and its facets. In this response to Morgeson et al. (2007), we comprehensively summarize previously published meta‐analyses on (a) the optimal and unit‐weighted multiple correlations between the Big Five personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
376
2
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 451 publications
(405 citation statements)
references
References 125 publications
13
376
2
14
Order By: Relevance
“…As previously discussed, personality measures have been shown to be valid predictors of future performance, both in concurrent studies using existing employees and in predictive validation studies using actual job applicants (Ones et al, 2007). However, the TAPAS did not contribute to the prediction of training success in a manner consistent with prior research, which has generally shown that personality can contribute small to moderate gains in the explanation of training success 64 (Barrick and Mount, 2001).…”
Section: Reexamine Role Of Personality Measuressupporting
confidence: 60%
“…As previously discussed, personality measures have been shown to be valid predictors of future performance, both in concurrent studies using existing employees and in predictive validation studies using actual job applicants (Ones et al, 2007). However, the TAPAS did not contribute to the prediction of training success in a manner consistent with prior research, which has generally shown that personality can contribute small to moderate gains in the explanation of training success 64 (Barrick and Mount, 2001).…”
Section: Reexamine Role Of Personality Measuressupporting
confidence: 60%
“…In terms of individual differences, there are few if any studies of individual innovation that examine compound personality traits as possible predictors, despite findings showing that compound traits are more valid predictors of other types of job behaviors than single personality traits, including those of the Five Factor Model (cf., Hough & Ones, 2001;Ones, Dilchert, Viswesvaran, & Judge, 2007). Also, studies of motivation factors other than intrinsic motivation are relatively few, especially in relation to self-regulatory factors shown to be related to goal-setting, persistence, and risk-taking in other performance domains.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…This increasing popularity of personality assessment has led to the development of a huge variety of inventories, all available commercially for researchers to apply in scientific studies, and for practitioners to use in organizations (Prewett, Tett, & Christiansen, 2013). Beyond more generic issues of the criterion-related validity of these proprietary personality measures (see, for instance, Ones, Dilchert, Viswesvaran, & Judge, 2007;Morgeson, Campion, Dipboye, Hollenbeck, & Schmitt, 2007), this abundance of inventories gives rise to questions about the convergence and divergence of their underlying structures (e.g. Anderson & Ones, 2003;Woods & Hardy, 2012).…”
Section: Personality Inventories In Organizational Assessmentmentioning
confidence: 99%